2012
DOI: 10.1227/neu.0b013e318246a4b1
|View full text |Cite
|
Sign up to set email alerts
|

Stent-Assisted Coiling of Wide-Necked Aneurysms in the Setting of Acute Subarachnoid Hemorrhage

Abstract: Our findings suggest that stent-assisted coiling and routine treatment with antiplatelet agents is a viable option in the management of ruptured wide-necked aneurysms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
50
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 41 publications
2
50
2
Order By: Relevance
“…The technique-related complication rate was 21% (13 of 61), with thromboembolic complications in 9 patients and aneurysm perforations in 4 patients. Amenta et al 1 reported a retrospective study of 65 patients with ruptured wide-necked aneurysms treated with SAC in whom there were 10 (15.38%) major complications associated with bleeding secondary to either antiplatelet thera- py or intraoperative in-stent thrombosis (5 patients each, 7.7%). Three patients (4.6%) suffered a fatal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The technique-related complication rate was 21% (13 of 61), with thromboembolic complications in 9 patients and aneurysm perforations in 4 patients. Amenta et al 1 reported a retrospective study of 65 patients with ruptured wide-necked aneurysms treated with SAC in whom there were 10 (15.38%) major complications associated with bleeding secondary to either antiplatelet thera- py or intraoperative in-stent thrombosis (5 patients each, 7.7%). Three patients (4.6%) suffered a fatal hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…1,25,27 Use of the SAC procedure has achieved excellent occlusion of the aneurysms and decreased the rates of angiographic recurrence. 12,27 In this study, follow-up angiographic results (mean 14.8 months) showed that 67.9% of aneurysms were completely occluded, which was improved compared with the immediate postembolization angiographic results (56.9% with complete occlusion).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported a 2.5% rate of in-stent stenosis in our series. 10 The following factors were tested for as predictors of recanalization: age, sex, ruptured aneurysm status, Hunt and Hess grade, aneurysm location, aneurysm size, previous aneurysm treatment, type of stent, stenting technique, staged treatment, procedural complications, delivery of coils before stent placement, immediate aneurysm occlusion, and follow-up time. In univariate analysis, predictors of recanalization were (1) older age (>65 years; P=0.01), (2) previously coiled aneurysms (P=0.02), (3) larger aneurysms (>10 mm; P<0.001), (4) incompletely occluded aneurysms (P=0.003), (5) Neuroform stent (P=0.1), (6) staged treatment (P=0.1), and (7) Of the 28 aneurysms treated with a telescoping stent technique, 19 had available angiographic follow-up at a mean time point of 16.7 months.…”
Section: Angiographic Outcomementioning
confidence: 99%